Inhibition of acyl‐ACP thioesterase as site of action of the commercial herbicides cumyluron, oxaziclomefone, bromobutide, methyldymron and tebutam. Issue 8 (17th June 2022) - Johnen, Philipp; Zimmermann, Sophie; Betz, Michael; Hendriks, Janneke; Zimmermann, Alexandra; Marnet, Martina; De, Inessa; Zimmermann, Gunther; Kibat, Christine; Cornaciu, Irina; Mariaule, Vincent; Pica, Andrea; et al.
Abstract: BACKGROUND: Understanding the mode and site of action of a herbicide is key for its efficient development, the evaluation of its toxicological risk, efficient weed control and resistance management. Recently, the mode of action (MoA) of the herbicide cinmethylin was identified in lipid biosynthesis with acyl‐ACP thioesterase (FAT) as the site of action (SoA). Cinmethylin was registered for selective use in cereal crops for the control of grass weeds in 2020. RESULTS: Here, we present a high‐resolution co‐crystal structure of FAT in complex with cumyluron identified by a high throughput crystallization screen. We show binding to and inhibition of FAT by cumyluron. Furthermore, in an array of experiments consisting of FAT binding assays, FAT inhibition assays, physiological and metabolic profiling, we tested compounds that are structurally related to cumyluron and identified the commercial herbicides oxaziclomefone, methyldymron, tebutam and bromobutide, with so far unknown sites of action, as FAT inhibitors. Additionally, we show that the previously described FAT inhibitors cinmethylin and methiozolin bind to FAT in a nanomolar range, inhibit FAT enzymatic activity and lead to similar metabolic changes. CONCLUSION: Based on presented data, we corroborate cinmethylin and methiozolin as potent FAT inhibitors and identify FAT as the SoA of the herbicides cumyluron, oxaziclomefone, bromobutide, methyldymron and tebutam. © 2022 Society of Chemical Industry. Abstract : Using a combination of structural biology, biochemistry, plant physiology and metabolomics, we identify inhibition of fatty acid thioesterase (FAT) as Mode of Action (MoA) for the commercial herbicides cumyluron, oxaziclomefone, bromobutide, methyldymron and tebutam, and corroborate FAT inhibition as MoA for cinmethylin and methiozolin.